2021
DOI: 10.3389/fphar.2021.651523
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Instrument for Measuring Adherence to Treatment With Immunomodulators in Patients With Multiple Myeloma

Abstract: Background: Validate the Treatment Adherence Measure (TAM) instrument in outpatients with MM concerning construct validity, reliability and the ceiling and floor effects.Methods: This cross-sectional study included patients diagnosed with MM previously treated with an immunomodulator for at least one month, aged 18 or over, and followed-up in the investigated outpatient clinics. Adherence to immunomodulators was measured by TAM. The TAM’s reliability was assessed using Cronbach’s alpha; The association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In a more recent study, the validation of the Treatment Adherence Measure (TAM) ( Silveira et al, 2021 ) in outpatients with multiple myeloma was unsatisfactory. That study reported very high adherence to treatment and a tendency to extreme responses, as in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a more recent study, the validation of the Treatment Adherence Measure (TAM) ( Silveira et al, 2021 ) in outpatients with multiple myeloma was unsatisfactory. That study reported very high adherence to treatment and a tendency to extreme responses, as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The first factor of our instrument distinguishes it from other adherence scales, and provides the opportunity to explore patients' thoughts, beliefs and expectations, and how these variables correlate to more or less adherent behavior. In addition, we responded to the floor/ceiling effect identified during the validation process by dichotomizing the responses (Yes/No), as in other published studies (Silveira et al, 2021;da Silva Carvalho et al, 2010). Criterion validity is important because it compares our results with the gold standard.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, MPR likely leads to an underestimation of lenalidomide adherence. Patient-reported adherence has been used as an alternative measure but is also not sufficiently reliable [8,9]. One recent study in Germany combined patient interviews with prescription data, survey of attending physicians, and caregiver interviews [10].…”
Section: Introductionmentioning
confidence: 99%